Synthèse des travaux : ier Symposium international de recherche en criminologie comparée, Mont-Gabriel, 30 avril–3 mai 1969 - Normandeau, André; Szabo, Denis (Acta Criminologica, 1970)
AbstractSYNTHESIS OF THE FIRST INTERNATIONAL SYMPOSIUM FOR RESEARCH IN COMPARATIVE CRIMINOLOGYIntroductionAt the beginning of the development of the social sciences there was a considerable vogue for comparative research. A long period of empirical studies and almost total preoccupation with methodological problems followed. Once again, however, psychology, political science, sociology, and above all anthropology, have taken up the thread of this tradition, and the bibliography in these fields is becoming ever more abundant. The study of deviance, of various manifestations of criminality, and of social reaction against crime are, however, noticeably missing in the picture, even though there is nothing in the nature of criminology which precludes the development of comparative research.To many research workers in criminology, the time seemed ripe to take up the comparative tradition once again. Two imperatives were considered : the generalization of norms of deviance which are tied to the standard of living set by industrial civilization, thus putting the problem of criminality in a global light ; and, second, the development and standardization of methods of studying these phenomena, drawing on the experience of allied disciplines.The response of the participants in this Symposium and the results of their discussions were not unexpected. A consensus was arrived as to the problems it was thought important to study, and agreement was reached about the strategies of research to be undertaken. Priorities, however, were not established since too much depends on the availability of research teams, funds, etc. But the broad, overall look at the main problems in comparative criminology will, hopefully, open a new chapter in the history of crimino-logical research and in our continuing search for knowledge of man and society.The brief resume which follows should give the reader an idea of the extent of the problems tackled. The detailed proceedings of the Symposium will be published at a later date, in mimeographed form.Sectors of research proposedIn a sense, this Symposium was prepared by all the participants. Theorganizers had requested that each person invited prepare a memorandum setting out the problems in comparative criminology which he considered to be most important. The compilation of their replies, reported to the plenary session at the opening of the Symposium, produced the following results :Summary of suggestions for research activitiesNote : In all that follows, it should be understood that all of these topics should be studied in a cross-cultural or international context.1) Definitions and concepts : a) Social vs legal concept of deviance ; b) Distinction between political and criminal crimes ; c) The law : a moral imperative or a simple norm ; d) The concepts used in penal law : how adequate ? e.g. personality of criminal ; e) Who are the sinners in different cultures and at different times.2) Procedures : a) Working concepts of criminal law and procedure ;b) Differentiating between factors relating to the liability-finding process and the sentencing process ; c) Behavioural manifestations of the administration of criminal justice ; d) Judicial decisions as related to the personality of the judges and of the accused ; e) Sentencing in the cross-national context (2 proposals) ; f) In developing countries, the gap between development of the legal apparatus and social behaviour ; g) Determination of liability ; h) The problem of definition and handling of dangerous offenders ; i) Decision-making by the sentencing judges, etc. (2 proposals) ; ;) Medical vs penal committals ; k) Law-enforcement, policing.3) Personnel : a) Professionalization in career patterns ; b) Criteria for personnel selection ; c) Greater use of female personnel.4) Causation. Situations related to criminality : a) How international relations and other external factors affect crime ; 6) Hierarchy of causes of crime ; c) Migrants. Minorities in general ; d) Relation to socio-economic development in different countries ; e) A biological approach to criminal subcultures, constitutional types, twin studies, etc. ; f) Cultural and social approach : norms of moral judgment, ideals presented to the young, etc. ; g) Effect of social change : crime in developing countries, etc. (6 proposals) ; h) Effects of mass media, rapid dissemination of patterns of deviant behaviour (2 proposals).5) Varieties of crime and criminals : a) Traffic in drugs ; b) Prison riots ; c) Violence particularly in youth (7 proposals) ; d) Dangerousness ; e) Relation to the rights of man (including rights of deviants); f) Female crime (2 proposals) ; g) Prostitution ; i) The mentally ill offender ; ;) Cultural variations in types of crime ; k) Organized crime ; /) Use of firearms ; m) Gambling ; n) Victims and victimology.6) Treatment : evaluation : a) Social re-adaptation of offenders ; b) Statistical research on corrections, with possible computerization of data ;c) Comparisons between prisons and other closed environments ; d) Extra-legal consequences of deprivation of liberty ; e) Rehabilitation in developing countries ; f ) Criteria for evaluation of programs of correction ; g) Biochemical treatment (2 proposals) ; i) Differential treatment of different types of offense. Evaluation ; /) Prisons as agencies of treatment ; k) Effects of different degrees of restriction of liberty ; /) Environments of correctional institutions ; m) Study of prison societies ; n) Crime as related to the total social system.7) Research methodology : a) Publication of what is known regarding methodology ; b) Methods of research ; c) Culturally-comparable vs culturally-contrasting situations ; d) Development of a new clearer terminology to facilitate communication ; e) Actual social validity of the penal law.8) Statistics : epidemiology : a) Need for comparable international statistics ; standardized criteria (3 proposals) ; b) Difficulties. Criminologists must collect the data themselves.9) Training of research workers : Recruiting and training of « com-paratists ».10) Machinery : Committee of co-ordination.DiscussionsThe discussions at the Symposium were based on these suggestions, the main concentration falling on problems of manifestations of violence in the world today, the phenomenon of student contestation, and on human rights and the corresponding responsibilities attached thereto.Although the participants did not come to definite conclusions as to the respective merits of the problems submitted for consideration, they did discuss the conditions under which comparative studies of these problems should be approached, the techniques appropriate to obtaining valid results, and the limitations on this type or work.Four workshops were established and studied the various problems. The first tackled the problems of the definition of the criteria of « danger » represented by different type of criminals ; the problem of discovering whether the value system which underlies the Human Rights Declaration corresponds to the value system of today's youth; the problem of the treatment of criminals ; of female criminality ; and, finally, of violence in the form of individual and group manifestations. The second workshop devoted its main consideration to the revolt of youth and to organized crime, also proposing that an international instrument bank of documentation and information be established. The third workshop considered problems of theory : how the police and the public view the criminal ; the opportunity of making trans-cultural comparisons on such subjects as arrest, prison, etc. ; and the role of the media of information in the construction of value systems. The fourth workshop blazed a trail in the matter of methodology appropriate to research in comparative criminology.The period of discussions which followed the report of the four workshops gave rise to a confrontation between two schools of thought within the group of specialists. The question arose as to whether the problem of student contestation falls within the scope of the science of criminology. Several experts expressed the opinion that criminologists ought not to concern themselves with a question which really belongs in the realm of political science.On the other hand, the majority of the participants appeared to feel that the phenomenon of student contestation did indeed belong in the framework of criminological research. One of the experts in particular took it upon himself to be the spokesman of this school of thought. There are those, he said, who feel that criminology should confine itself and its research to known criminality, to hold-ups, rape, etc. However, one should not forget that penal law rests on political foundations, the legality of power, a certain moral consensus of the population. Today, it is exactly this « legitimate » authority that is being contested. Is it not to be expected, therefore, that criminology should show interest in all sociological phenomena which have legal and criminal implications ? Contestation and violence have consequences for the political foundations of penal law, and therefore are fit subjects for the research of the criminologist.International Centre {or Comparative CriminologyThe First International Symposium for Research in Comparative Criminology situated itself and its discussions within the framework and in the perspectives opened by the founding of the International Centre for Comparative Criminology. The Centre is sponsored jointly by the University of Montreal and the International Society for Criminology, with headquarters at the University of Montreal. As one of the participants emphasized, criminologists need a place to retreat from the daily struggle, to meditate, to seek out and propose instruments of research valid for the study of problems common to several societies. Viewing the facts as scientists, we are looking for operational concepts. Theoreticians and research workers will rough out the material and, hopefully, this will inspire conferences and symposiums of practitioners, jurists, sociologists, penologists, and other specialists. Above all, it will give common access to international experience, something which is lacking at present both at the level of documentation and of action. A bank of instruments of method-ology in the field of comparative criminology does not exist at the present time. The Centre will undertake to compile and analyse research methods used in scientific surveys, and it will establish such an instrument bank. It will also gather and analyse information pertaining to legislative reforms now in progress or being contemplated in the field of criminal justice. Through the use of computers, the Centre will be able to put these two projects into effect and make the results easily accessible to research workers, and to all those concerned in this field.The participants at the Symposium were given a view of the extent of the problems envisaged for research by the future Centre. It is hoped that this initiative will be of concrete use to research workers, private organizations, public services and governments at many levels, and in many countries.